Factors Influencing the Relationship Quality between Exporters and Foreign Intermediaries on SMEs Export Performance (Journal of International Studies, 2019)
This study aims to investigate factors that influence the relationship quality between Malaysia SMEs exporter and foreign intermediaries. This paper draws insights from two integrating theories such as social capital theory (SCT) and internationalization process (IP) theory to evaluate the synergistic consequences of several constructs such as cultural similarity, effective communication, knowledge sharing and trust on export performance. The model is tested using Structural Equation Modeling (SEM) via Smart PLS on a sample of 203 SME exporters in Malaysia. The findings revealed that all hypotheses are supported. The research highlights that cultural similarity is a catalyst in internationalization process and show the mechanism on how cultural similarity can influence effective communication and knowledge sharing thus impetus trust which finally reflect the performance outcomes. The findings extended the application of the underpinning theories and their tenets in explaining the Malaysian SMEs’ export performance use foreign intermediaries.